The Influence of Fly Ash Type on Properties of Cements Composites - Katarzyna SYNOWIEC (Engineering Transactions, 2015)
This paper presents the results of tests carried out on mortars prepared with fly ash – slag cements. Two types of fly ash were used – siliceous (V) and calcareous (W). The influence of fly ash type on properties of mortars was evaluated on the base of results of following tests: compressive strength, consistency and its stability in time and chloride ions permeability and carbonation depth. It was claimed that mortars made with cements containing calcareous fly ash (W) are characterized by higher compressive strength (at each age). Moreover, negative impact of calcareous fly ash (W) on rheological properties of mortars was observed. Durability tests revealed favourable effect of calcareous fly ash on resistance of mortars to corrosive agents attack – lower chloride ions permeability and carbonation depth in comparison to siliceous fly ash – slag cement mortars.